Effectiveness of Physiotherapy on Freezing of Gait in Parkinson's Disease: A Systematic Review and Meta‐Analyses. Issue 4 (4th December 2019) - Cosentino, Carola; Baccini, Marco; Putzolu, Martina; Ristori, Diego; Avanzino, Laura; Pelosin, Elisa
Abstract: Freezing of gait is considered one of the most disabling gait disorders in patients with PD. An effective treatment for freezing of gait is missing, thus current management requires a multidisciplinary approach. Among treatment options, physiotherapy is acknowledged to be crucial; however, a systematic review that demonstrates its efficacy is missing. This review aims at examining the short‐ and long‐term effects of physiotherapy in improving freezing of gait in PD patients. Five electronic databases were searched for English‐language full‐text articles, and only randomized controlled trials were considered. The freezing of gait questionnaire was selected as the primary outcome measure because it is the only validated measure used to evaluate the severity and impact of freezing of gait on patients' daily life. From 1, 130 trials, 19 relevant studies, including 913 patients, were selected. The included studies varied for sample size, methodology, and type of intervention. None of the studies had a low risk of bias, but the majority of randomized control trials presented a low risk for at least 6 of 13 biases. Our findings provide evidence for short‐term effectiveness of physiotherapy in improving freezing of gait (physiotherapy vs. no treatment: effect size = –0.28 [–0.45, –0.11], P = 0.001; physiotherapy vs. control: effect size = 0.43 [–0.65, –0.21], P  < 0.0001), particularly when tailored interventions are applied. These results seem to be maintained at the follow‐up examinations (effect size = –0.52 [–0.78, –0.26]; P = 0.001). Promising findings on the potential benefits of physiotherapy in improving freezing of gait were found, although further randomized control trial studies are still needed. Questions remain on the type and duration of intervention that best fits for treating freezing of gait symptom in PD. © 2019 International Parkinson and Movement Disorder Society